Analysis of the Factors that Influence the Incidence of Low Birth Weight (BBLR) in Bojonegoro District - Wahyu Rusmitawati; Byba Melda Suhita; Ratna Wardani (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Low Birth Weight is health problems that need to be addressed seriously because is an indicator to determine health level of the nation. South East Asia has 20-35 % of infants born with Low Birth Weight and 70-80% neonates were death because of premature infants and Low Birth Weight. In Bojonegoro district since 3 years ago, has fluctuated cases of Low Birth Weight. The purpose of this research to know the impact of nutritional status of mothers, gestational age, disorder/comorbidities of disorder, exposure to cigarette smoke, parity and regularity examination pregnancy relating Low Birth Weight in Bojonegoro district. The methodology of this research is analytic correlational by approach cross sectional. The population research is all women rise in November 2019- January 2020 in public health center area Balen, Ngasem, Kedungadem Bojonegoro district. The technique of this research used proportional random sampling by using 133 samples. Analysis techniques data using regression double logistics. The result showed that a variable that influence the incidence Low Birth Weight is the nutritional status (p=0,000), disorder/ comorbidities of comorbidities (p=0,013) and parity (p=0,008). While variables that not affected to Low Birth Weight is gestational age, exposure to cigarette smoke and regularity examination pregnancy. Six variables with negelkerke has value R= 0,658 capable of being explained Low Birth Weight factors influencing the cases.